A new composite connector for timber-concrete composite structures. (1st June 2016) - Auclair, Samuel C.; Sorelli, Luca; Salenikovich, Alexander
Graphical abstract: Highlights: A new elongated composite connector has been developed for timber concrete composite structures. The stiffness and strength of the connection depend on the external and internal diameters of the connector, respectively. The non-linear Winkler beam model well reproduces the shear connection. The composite connector diameters control the deflection and the structural ductility. Abstract: Timber-concrete composite (TCC) structures are emerging in several industrial applications as an efficient method for optimizing the structural performance and the cost of construction. Their effectiveness depends strongly on the kind of connection employed. In order to guarantee sufficient ductility to the structure without sacrificing its stiffness and strength, the connections have to be rigid, strong and deform plastically before the brittle collapse of the timber or concrete members. This work presents a new composite connector, which can be used to enhance the ductility of a structure without significant loss of stiffness at serviceability limit states. The studied composite connector consists of a composite cylinder made of ultra-high performance fibre-reinforced concrete (UHPFRC) shell with a steel cylindrical core. The UHPFRC enhances micro-cracking resistance and energy dissipation under large deformations. Performance characteristics of the connectors of various sizes have been evaluated using shear tests of connections. The results show that the connection stiffness is principally governed by the diameter of the concrete shell, while the connection resistance is principally governed by the diameter of the steel core. A beam on a Winkler foundation model has been applied to describe the behaviour of the composite connector in the shear tests. Finally, the composite beam theory has been applied to predict the structural behaviour of TCC beams with different parameters of the composite connectors. The results show that the diameters of the concrete shell and of the steel core of the connector can be conveniently varied to optimize the TCC beam performance by significantly enhancing its structural ductility without significant loss of flexural stiffness and load bearing capacity.